EFFECT OF MATERIAL ANISOTROPY ON THE ONSET OF CONVECTIVE FLOW IN THREE-DIMENSIONAL FLUID-SATURATED FAULTS - Zhao Ch.; Hobbs B.E.; Ord A.; Muhlhaus H.B.; Lin Ge. (My University, 2003)
In order to investigate the effect of material anisotropy on convective instability of three-dimensional fluid-saturated faults, an exact analytical solution for the critical Rayleigh number of three-dimensional convective flow has been obtained. Using this critical Rayleigh number, effects of different permeability ratios and thermal conductivity ratios on convective instability of a vertically oriented three-dimensional fault have been examined in detail. It has been recognized that (1) if the fault material is isotropic in the horizontal direction, the horizontal to vertical permeability ratio has a significant effect on the critical Rayleigh number of the three-dimensional fault system, but the horizontal to vertical thermal conductivity ratio has little influence on the convective instability of the system, and (2) if the fault material is isotropic in the fault plane, the thermal conductivity ratio of the fault normal to plane has a considerable effect on the critical Rayleigh number of the three-dimensional fault system, but the effect of the permeability ratio of the fault normal to plane on the critical Rayleigh number of three-dimensional convective flow is negligible.
Keywords: CONVECTIVE INSTABILITY; CRITICAL RAYLEIGH NUMBER; THREE-DIMENSIONAL FAULT; MATERIAL ANISOTROPY; ANALYTICAL SOLUTION